FREKUENSI TINGKAT PERTENGKARAN TERUS MENERUS (SYIQá¾¹Q) SEBAGAI ALASAN PERCERAIAN DI PENGADILAN AGAMA - Nasution, Muhammad Yusuf (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
The high rate of divorce that occurs in society is caused by several factors, including; due to disharmony, no responsibility, and economic problems. Among divorce cases, the most filed for divorce are from the wife. There are several reasons for divorce regulated by Islamic Law, Marriage Law Number 1 of 1974 in conjunction with Law Number 9 of 1975, and the Compilation of Islamic Law, including, disputes and quarrels that occur continuously as reasons for divorce. However, Islamic Law, Marriage Law Number 1 of 1974 in conjunction with Government Regulation Number 9 of 1975, and the Compilation of Islamic Law, do not explicitly stipulate in detail the minimum time limit for marriage to be able to file for divorce for this reason, and there is no explanation any reason belongs to the constant strife and bickering. This causes multiple interpretations, because the scope is too broad, so many things are used as reasons for disputes and fights for divorce, and later it can become one of the drivers of divorce which is too easy to do in people's lives. The Marriage Law cannot determine a minimum time limit for disputes and continuous bickering as reasons for divorce, because divorce is a human right.